PROGRAM DEVELOPMENT OF RESOURCE CENTER (RC) OF SLBN A CITEREUP TO SUPPORTING THE IMPLEMENTATION OF INCLUSIVE EDUCATION SYSTEM IN THE CITY OF CIMAHI (International Conference on Elementary Education, 2018)
Children with Special Needs is Children with special educational needs, which in learning needs special education service, to optimizing their potency. Reguler school in inclusive setting expected increase their social skills so that they are not get education service in segregation style and they are not exclusive, and expected they are can joint with community or event in society after they graduate from the school. School with inclusive education system needs qualified support like system support,regulation support, and professional support. For that presence Resource Center (RC) SLBN A Citereup (Citereup State Special School for Blind) is expected to help the implementation of inclusive education especially in the city of Cimahi. this research was conducted in the city of Cimahi , precisely at Source Center of Resource Center (RC) SLBN A Citereup Cimahi with 6 elementary and junior high schools which provide Inclusive Education system in the city of Cimahi as target of development of program based on Assessment needs developed by the Resource Center (RC) of SLBN A Citereup Cimahi .Research method used in this research is qualitative of Desckriptif Analytic. The result showed that most regular school with inclusive education system needed kind of developing program from Resource Center like center of professional support provider to training teacher who teaching in regular school with inclusive education system , sunch as how to Identification, Assesment, and give education service for student with special needs in school with inclusive education system at elemntary and Junior High School level in the City of Cimahi.